The Population Cost-Effectiveness of Weight Watchers with General Practitioner Referral Compared with Standard Care - Lymer, S.; Schofield, D.; Cunich, M.; Lee, Crystal; Fuller, N.; Caterson, I.; Colagiuri, S. (Nature Publishing Group, 2018)
© 2018 The Obesity Society Objective: This study aimed to assess population-level cost-effectiveness of the Weight Watchers (WW) program with doctor referral compared with standard care (SC) for Australian adults with overweight and obesity. Methods: The target population was Australian adults = 20 years old with BMI = 27 kg/m2, whose obesity status was subsequently modeled for 2015 to 2025. A microsimulation model (noncommunicable disease model [NCDMod]) was used to assess the incremental cost-effectiveness of WW compared with SC. A health system perspective was taken, and outcomes were measured by obesity cases averted in 2025, BMI units averted for 2015 to 2025, and quality-adjusted life years for 2015 to 2025. Univariate sensitivity testing was used to measure variations in the model parameters. Results: The WW intervention resulted in 60,445 averted cases of obesity in 2025 (2,311 more cases than for SC), extra intervention costs of A$219 million, and cost savings within the health system of A$17,248 million (A$82 million more than for SC) for 2015 to 2025 compared with doing nothing. The modeled WW had an incremental cost-effectiveness ratio of A$35,195 in savings per case of obesity averted in 2025. WW remained dominant over SC for the different scenarios in the sensitivity analysis. Conclusions: The WW intervention represents good value for money. The WW intervention needs serious consideration in a national package of obesity health services.